Stunted Growth Caused by Blast Disease in Rice Seedlings Is Associated with Changes in Phytohormone Signaling Pathways - Jiang, Chang-Jie; Liu, Xiao-Long; Liu, Xin-Qiong; Zhang, Hui; Yu, Ying-Jie; Liang, Zheng-Wei (Frontiers in Plant Science, 2017)
In response to pathogen attack, plants prioritize defense reactions generally at the expense of plant growth. In this work, we report that changes in phytohormone signaling pathways are associated with the stunted plant growth caused by blast disease in rice seedlings. Infection of rice seedlings with blast fungus Magnaporthe oryzae (race 007.0) at the four-leaf stage (three true leaves) resulted in considerable inhibition of the growth of the upper uninfected distal leaves; the length of leaf blade and leaf sheath of the sixth and seventh leaf was reduced by 27% and 82%, and 88% and 72%, respectively, compared to that in the uninoculated plant control. Interestingly, cutting off the blast-infected fourth leaf within 2 days post inoculation (dpi) significantly rescued the inhibition of leaf growth, implying that an inhibitory substance(s) and/or signal was generated in the blast-infected leaves (fourth leaf) and transmitted to the upper distal leaves (sixth and seventh) during the 2-dpi period that induced growth inhibition. Expression analysis of marker genes for phytohormone pathways revealed acute activation of the jasmonate (JA) and abscisic acid (ABA) signaling pathways, and repression of auxin, gibberellic acid (GA) and salicylic acid (SA) signaling pathways, in the sixth leaf. The genes related to cell wall expansion were also significantly downregulated. In the blast-infected fourth leaf, JA pathway was activated within 2 dpi, followed by activation of ABA pathway 3 dpi. Further, leaf inhibition caused by blast infection was partially rescued in the rice mutant line coleoptile photomorphogenesis 2 (cpm2), which is defective in the gene encoding allene oxide cyclase (OsAOC). These results indicate that the JA signaling pathway is at least partly involved in the growth inhibition processes. Collectively, our data suggest that, upon pathogen attack, rice seedlings prioritize defense reactions against the infecting pathogen by temporarily ceasing plant growth through the systemic control of phytohormone pathways.